Return to the ice palace - David, Erica (David, Erica. Anna & Elsa, 2016)
Anna and Elsa are hosting very important guests - and what better way to impress than to show them the beautiful ice palace Elsa created high in the mountains? But their visitors get a big surprise when the ice palace is taken over by Elsa's tiny snowgies!